2012
DOI: 10.1080/20786204.2012.10874224
|View full text |Cite
|
Sign up to set email alerts
|

Pain as a reason for primary care visits: cross-sectional survey in a rural and periurban health clinic in the Eastern Cape, South Africa

Abstract: Background: The burden of pain in primary care has not been described for South Africa. This study aimed to determine the prevalence of pain in primary care and to characterise pain among adult patients attending a rural and a periurban clinic in the Eastern Cape (EC) Province. Method:A cross-sectional descriptive survey was conducted among adult patients attending a rural and periurban clinic over four days. Consecutive patients were asked whether they were in the clinic because of pain and whether the pain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…More than half of the patients reported that they had pain. This is similar to previous reports that pain is a common complaint in general medical practice [21,22]. About two-thirds of the patients had anxiety symptoms while close to a half had depressive symptoms.…”
Section: Sociodemographic/clinical Characteristics Of Patientssupporting
confidence: 91%
“…More than half of the patients reported that they had pain. This is similar to previous reports that pain is a common complaint in general medical practice [21,22]. About two-thirds of the patients had anxiety symptoms while close to a half had depressive symptoms.…”
Section: Sociodemographic/clinical Characteristics Of Patientssupporting
confidence: 91%
“…Despite pain being the most common symptom that patients present with to hospital, healthcare workers inadequately assess and treat pain. 5 This study evaluates the pain knowledge and attitudes of 2018 final-year medical students (104 students, 44.8%). Our sample size allows 90% confidence in the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Despite pain being the most common symptom that patients present with to hospital, healthcare workers inadequately assess and treat pain. 5 This study evaluates the pain knowledge and attitudes of 2018 final-year medical students There is no gold standard instrument currently used to assess knowledge, perceptions and attitudes to pain management. Knowledge about pain management amongst nursing and medical students is consistently generally poor, despite the diversity of standardised instruments used to evaluate it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain had a severe impact on sleep quality in 39.2% patients, walking ability (37.4%), routine housework (33.8%), mood (20.1%), interpersonal relationships (15.3%) and enjoyment of life (16.3%). [7][8][9]…”
Section: Introductionmentioning
confidence: 99%